SCENARIO ANALYSIS OF ECONOMIC FEASIBILITY IN THE UTILIZATION OF PUBLIC SPACE (CASE STUDY: KEBUN BUNGAN STADIUM MEDAN) - Ayu Pratiwi Anggraini; Anthoni Veery Mardianta; Gina Cynthia Raphita Hasibuan (SOSIOEDUKASI, 2026)
Kebun Bunga Stadium is one of public spaces provided by the Government of Medan. Over time, there has been a decline in performance including facilities that are starting become obsolete and limited sports infrastructure due to lack of maintenance. Therefore under these conditions, Kebun Bunga Stadium was revitalized as a form of effort to meet the training infrastructure for athletes in order to realize the capital of North Sumatera as a city of athletes. The revitalization is multi-year contract used regional budget (APBD) 2023 and 2024 with a total cost are Rp. 191,665,325,000. Kebun Bunga Stadium has several facilities such as an international-standard soccer field, tennis courts, volleyball courts, rock climbing walls, a skate park, a gym, a playground, an indoor sports field, a water park, a jogging track, and others. After revitalization, there are several sports facilities will be subject to fees, which will be used as a buffer for maintenance costs and a source of regional revenue. However, there is no clear information about public perception of these fees. Furthermore, every project supported by government must generate economic and social benefits for the community. Therefore, the benefits obtained must be greater than the costs incurred in order to support the sustainable facility. To understand this issue, a questionnaire was distributed to determine the public perception fees and scenario analysis of economic feasibility to ensure the feasibility and sustainability of the public space.